Bioindication of trace metal pollution in the atmosphere of Baku city using ligustrum japonicum, olea europea, and pyracantha coccinea leaves - Youssef, Naglaa; Markert, Bernd; Gurbanov, Elshad; Sevnic, Haciyeva; Wünschmann, Simone (Journal of Environmental Engineering and Landscape Management, 2014)
The leaves of Ligustrum japonicum (Oleaceae), Olea europaea (Oleaceae), and Pyracantha coccinea (Rosaceae) were evaluated with the aim of using them as bioindicators for trace metal contamination in Baku city, Azerbaijan, one of the most highly polluted cities worldwide. These species of trees are the most abundant in urban and rural areas of Azerbaijan, because of high tolerance against climatic influences due to their modesty and adaptability. Concentrations of Cd, Cr, Cu, Fe, and Pb were determined in the leaves by AAS method. The samples were collected at three locations with different degrees of trace metal pollution (industrial, high traffic, and reference [botanical garden] site). The highest element concentrations were detected at sites of high traffic. Up to 70 times higher Pb concentrations could be found in the leaves of the trees that reflect the known Pb problem around Baku. The results presented give a first impression of a correlation between the degree of trace metal contamination in the environment and the trace metal concentration in the leaves of L. japonicum and O. europaea